2012
DOI: 10.1371/journal.pone.0044339
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intact Arabidopsis thaliana Leaf Transcript Profiles during Treatment with Inhibitors of Mitochondrial Electron Transport and TCA Cycle

Abstract: Plant mitochondria signal to the nucleus leading to altered transcription of nuclear genes by a process called mitochondrial retrograde regulation (MRR). MRR is implicated in metabolic homeostasis and responses to stress conditions. Mitochondrial reactive oxygen species (mtROS) are a MRR signaling component, but whether all MRR requires ROS is not established. Inhibition of the cytochrome respiratory pathway by antimycin A (AA) or the TCA cycle by monofluoroacetate (MFA), each of which initiates MRR, can incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 102 publications
(168 reference statements)
6
25
0
Order By: Relevance
“…Considering only transcripts that showed a more than 50-fold (Supplemental Table S1) increase in aox1a:rpoTmp revealed a largely unique response, and although many of these genes were up-regulated in aox1a, the magnitude of change in aox1a:rpoTmp was 10-to 100-fold greater. The pathogen response-like changes that have been noted previously in response to AOX1a inactivation (Schwarzländer et al, 2012;Umbach et al, 2012) seemed to be greatly increased in aox1a:rpoTmp under adverse growth conditions. Thus, exposure of plants impaired in both the cytochrome and the alternative respiratory chain to MLD stress seems to turn off the mitochondrial stress response observed in these plants under standard conditions.…”
Section: Distinct Transcriptomic Responses To Mitochondrial Respiratosupporting
confidence: 51%
See 2 more Smart Citations
“…Considering only transcripts that showed a more than 50-fold (Supplemental Table S1) increase in aox1a:rpoTmp revealed a largely unique response, and although many of these genes were up-regulated in aox1a, the magnitude of change in aox1a:rpoTmp was 10-to 100-fold greater. The pathogen response-like changes that have been noted previously in response to AOX1a inactivation (Schwarzländer et al, 2012;Umbach et al, 2012) seemed to be greatly increased in aox1a:rpoTmp under adverse growth conditions. Thus, exposure of plants impaired in both the cytochrome and the alternative respiratory chain to MLD stress seems to turn off the mitochondrial stress response observed in these plants under standard conditions.…”
Section: Distinct Transcriptomic Responses To Mitochondrial Respiratosupporting
confidence: 51%
“…6), and rather, a reaction akin to a response to pathogen infection is triggered. Note that earlier analyses have shown that responses to pathogen infection overlap with those to mitochondrial dysfunction, such as the response induced by treatment with antimycin A (Schwarzländer et al, 2012;Umbach et al, 2012). The prevalence of pathogen response-like changes could be because of an increase of this response in aox1a:rpoTmp exposed to adverse growth conditions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…First, restricted mitochondrial electron transport is expected to generate more superoxide/H 2 O 2 (Møller, 2001), and the accumulation of mitochondrial and extramitochondrial antioxidant transcripts was previously observed using inhibitors of the respiratory chain (Vidal et al, 2007;Umbach et al, 2012). Accordingly, transcripts of AOX1 and NDB2, which are responsive to H 2 O 2 (Wagner, 1995), accumulate in cls1 (Figure 7), as reported previously in Nicotiana sylvestris (Sabar et al, 2000;Dutilleul et al, 2003b;Vidal et al, 2007), maize (Zea mays; Karpova et al, 2002), and Arabidopsis CI mutants (Meyer et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
“…However, mitochondrial RTG signaling not only regulates the expression of mitochondrial proteins but also more generally reprograms nuclear gene expression affecting various subcellular compartments and functions (Fig. 6B) (221). Transcript groups encoding proteins involved in photosynthetic light reactions, organellar and cytosolic ribosome composition, as well as pathogen response were recently identified as common targets of regulation under mitochondrial respiratory dysfunction in Arabidopsis (195).…”
Section: The Retrograde Responsementioning
confidence: 99%